HUBUNGAN ANTARA VARIASI DAN MOTIVASI MENGAJAR GURU TERHADAP HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Riska Meliasari; Sri Sami Asih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Teaching variety and motivation are factors that can affect student learning outcomes. Based on the results of interviews, teachers have not fully implemented teaching variations in the learning process, as a result students experience boredom in learning. Teachers need to have teaching variations so that learning becomes active and fun, so that learning outcomes are optimal. Student learning outcomes are also influenced by teacher teaching motivationThe purpose of this study was to examine the relationship between teachers' teaching variation and teaching motivation on learning outcomes of Science and Social Studies (IPAS) of elementary school students in Kemuning and Wijaya Kusuma Gugus, Ngaliyan Sub- district, Semarang City. This research used quantitative method with correlation research type. The population in this study was 104 teachers. Sampling using Nonprobability Sampling method, while the sampling method used is saturated sampling of the population. Data collection techniques using questionnaires, observation, interviews, and documentation. The results showed a significant relationship between teacher teaching variation and teacher teaching motivation on IPAS learning outcomes with rcount= of 0.526 and Fcount of 40.681 and contributed 51.7%. From the results of the study it can be concluded that there is a significant relationship between teacher teaching variation and teacher teaching motivation to the learning outcomes of IPAS elementary school students Kemuning Cluster and Wijaya Kusuma Cluster Ngaliyan District Semarang City.